Active Vibration Control Through Quasi-Polynomial Based Controller. Issue 18 (2019) - Tliba, Sami; Boussaada, Islam; Bedouhene, Fazia; Niculescu, Silviu-Iulian
Abstract: This paper is about the problem of the vibration damping for a thin flexible beam, with an Euler-Bernoulli configuration, thanks to a new type of output feedback controller based on delayed proportional actions. The considered beam is equipped with two piezoelectric patches: one of them works as a sensor and the other as an actuator. Each one of them is bonded on one side of the beam and both are collocated. The model of this system is obtained numerically with a finite element modeling, leading to a linear state-space model. This paper addresses the design of a controller based on proportional and delayed-proportional actions on the input and output signals. The purpose of this work is to investigate the properties of the proposed output feedback controller in terms of vibration damping and of robustness. This controller is based on a rightmost-characteristic root assignment approach. Simulation results show the effectiveness of this controller design method and its ability to assign several poles of a linear system with fewer degrees of freedom than a minimal order linear controller with the usual pole placement technique.